Analysis of Sale and Purchase Deed Made before Land Deed Making Officials in Gianyar Regency - Ni Putu Tryana Tresna Dewi; Ni Made Jaya Senastri; I Nyoman Alit Puspadma (Journal of Legal and Cultural Analytics, 2025)
In order to comply with the principle of freedom of contract, this study examines the content of sale and purchase deeds made before Land Deed Making Officials in Gianyar Regency as well as their form in relation to Article 1868 of the Civil Code. According to this study's findings, the sale and purchase agreement executed in front of Gianyar Regency's Land Deed Making Officer, in accordance with Article 1868 of the Civil Code, is a legitimate document. Although the form and content of the act are regulated by this Ministerial Regulation, its annexes may restrict flexibility and run the danger of breaching the law if the parties' agreement is not accommodated.